KIMMERIDGIAN-TITHONIAN SEA-LEVEL FLUCTUATIONS IN THE ULJANOVSK-SARATOV BASIN (RUSSIAN PLATFORM) - Zorina S.O.; Ruban D.A. (My University, 2007)
The Uljanovsk-Saratov Basin, located in the southeast of the Russian Platform, presents an intriguing record of the Kimmeridgian-Tithonian sea-level fluctuations. In the Late Jurassic, this basin was a trough within the Interior Russian Sea. The data available from both outcrops and boreholes have permitted outlining a number of lithostratigraphic units and regional hiatuses in the northeastern segment of the Uljanovsk-Saratov Basin, thus permitting a precise reconstruction of transgressions/regressions and deepenings/ shallowings. In total, three transgressive-regressive cycles and two deepening pulses have been established. These regionally documented changes were both related in part to global eustatic changes, and they also corresponded in part to the regional sea-level changes in some basins of Western Europe and Northern Africa, but not to those of the Arabian Platform. Differences observed between the global and regional curves as well as rapid Tithonian sealevel oscillations are explained by the influences of tectonic activity. It is hypothesized that the regional Tithonian oxygen depletion might have been a consequence from the rapid flooding of a densely vegetated land.
Keywords: SEA LEVEL; TRANSGRESSION; REGRESSION; EUSTASY; OXYGEN DEPLETION; ULJANOVSK-SARATOV BASIN; RUSSIAN PLATFORM; KIMMERIDGIAN; TITHONIAN; Mesozoic::Jurassic::Upper::Kimmeridgian; Мезозой::Юрская::Верхний::Киммериджский; Mesozoic::Jurassic::Upper::Tithonian; Мезозой::Юрская::Верхний::Титонский